Implementasi Pendidikan Agama Islam dalam Pembentukan Karakter Religius Peserta Didik di SMPIT Ar Rahmah Pacitan - Mahendra, Arya Aditya; Riyanto, Ridho (Lembaga Yasin AlSys, 2025)
This study examines the implementation of Islamic Religious Education (PAI) in the formation of religious character of students at SMPIT Ar Rahmah Pacitan, against the background of weak internalization of religious values among adolescents. The study aims to analyze the implementation of PAI as well as its supporting and inhibiting factors. Using a descriptive qualitative approach with a case study design, data were collected through interviews, observations, and documentation studies. The results showed that intracurricular, co-curricular, and school religious culture activities were generally effective in shaping students' religious character, supported by exemplary teachers, routine religious programs, and parental support. The main obstacles include inconsistency of habituation at home, limited learning innovation, and the negative influence of social media. The discussion confirms the importance of habituation and exemplary as a stimulus for behavior change according to behavioristic theory. This study concludes that the integration of religious education with school culture plays a significant role in shaping religious character, and proposes innovation in learning methods and more intensive family involvement to overcome the challenges of the digital era.